2017
DOI: 10.1021/acsnano.7b00622
|View full text |Cite
|
Sign up to set email alerts
|

Podosome Force Generation Machinery: A Local Balance between Protrusion at the Core and Traction at the Ring

Abstract: Determining how cells generate and transduce mechanical forces at the nanoscale is a major technical challenge for the understanding of numerous physiological and pathological processes. Podosomes are submicrometer cell structures with a columnar F-actin core surrounded by a ring of adhesion proteins, which possess the singular ability to protrude into and probe the extracellular matrix. Using protrusion force microscopy, we have previously shown that single podosomes produce local nanoscale protrusions on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 41 publications
8
80
0
1
Order By: Relevance
“…It is generally accepted that podosome-mediated protrusive force generation is regulated by an interplay between actin polymerization and myosin IIA activity (21,22,42). Furthermore, recent in silico modelling of podosome force distribution strongly suggested that protrusive force generation in the core is balanced by local pulling force in the ring at the level of single podosomes (20). An explanation, however, for how protrusive and pulling forces are transmitted within the podosome structure remained elusive since no clear structural connection between the core and the ring has been described so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that podosome-mediated protrusive force generation is regulated by an interplay between actin polymerization and myosin IIA activity (21,22,42). Furthermore, recent in silico modelling of podosome force distribution strongly suggested that protrusive force generation in the core is balanced by local pulling force in the ring at the level of single podosomes (20). An explanation, however, for how protrusive and pulling forces are transmitted within the podosome structure remained elusive since no clear structural connection between the core and the ring has been described so far.…”
Section: Discussionmentioning
confidence: 99%
“…Neighboring podosomes are interconnected by a network of actin filaments that radiate from the podosome core and facilitate a mesoscale (1.5-10 µm) connectivity (17)(18)(19). While individual podosomes are thought to function as micronsized protrusive machineries (20)(21)(22), their mesoscale connectivity presumably facilitates long-range basement membrane exploration for protrusion-permissive spots (18,23). An adequate structural framework, however, that explains podosome protrusion and mechanosensing is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 1C, we compare the reconstructions of the same sample of tagged F-actin network in podosomes 123 obtained by second-order statistics dSTORM (NanoJ software, Super Resolution Radial Fluctuation) 124 (Gustafsson et al, 2016) and RIM. Podosomes are actin-rich, cell adhesion structures applying protrusive 125 forces on the extra cellular environment, recently observed by 3D dSTORM (Bouissou et al, 2017).…”
mentioning
confidence: 87%
“…Talin can adopt multiple conformations in the cell, ranging from a head to tail auto-inhibited conformation to a fully extended, integrin and actin bound mechanically stretched conformation (Yao et al, 2016). To evaluate the 3D FA distribution of talin as well as its vertical extension, we imaged both N-terminally (talin-N) and C-terminally (talin-C) tagged talin-1 (Liu et al, 2015;Bouissou et al, 2017). Overall, the Z-position values for talin-N ( Z centre =72.8± 12.3 nm ) and for talin-C ( Z centre =103.5± 20.5 nm ) are higher than those reported for U2OS cells (Liu et al, 2015).…”
Section: Talin Is Fully Extended Throughout the Cornerstone Focal Adhmentioning
confidence: 99%